Optimization of Association Rule in Horizontally Distributed Databases: A new way to strengthen the security of Encrypted Data (International Journal of Advanced Research in Science, Management and Technology, 2016)
The proposed work describes the optimization of Association Rule for the distributed databases in terms of speed, memory used while transaction of distribution as well as extracting the data from various data sources in the network. The proposed work shall have two parts including distribution of data using Association rule and ensuring the search to be redirected to specific source based on key values used to create the sub set in association rule. The availability shall be tested by verifying if the specific source is ready or not if not the search for that part shall only be carried out on the server itself.
Keywords: Distributed Databases, Association rule, Database Mining, Database Security